2007
DOI: 10.1071/mf06233
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hooking damage and hook type on post-release survival of sand flathead (Platycephalus bassensis)

Abstract: This study examined post-release survival in sand flathead (Platycephalus bassensis) and whether there were survival benefits from the use of circle hooks over conventional hook patterns. Anatomical hooking location was the major factor contributing to mortality, with an almost 100% survival rate for fish hooked in the lip, mouth or eye (shallow-hooked) compared with around 64% for fish hooked in the throat or gut (deep-hooked). Mortality in deep-hooked fish was generally associated with injuries to vital orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
23
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 27 publications
6
23
2
Order By: Relevance
“…The shallow-hooking rate in A. butcheri was strongly influenced by fish length with shallow-hooking decreasing as fish length increased. The same trend was previously reported for A. butcheri (Grixti et al, 2007) and similar trends have been noted for black sea bass (Centropristis striata) (Bugley and Shepherd, 1991), brook trout (Salvelinus fontinalis) (Nuhfer and Alexander, 1992) and sand flathead (Platycephalus bassensis) (Lyle et al, 2007). In those studies, smaller fish were believed less likely to deeply engulf a hook because of their smaller mouth size.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The shallow-hooking rate in A. butcheri was strongly influenced by fish length with shallow-hooking decreasing as fish length increased. The same trend was previously reported for A. butcheri (Grixti et al, 2007) and similar trends have been noted for black sea bass (Centropristis striata) (Bugley and Shepherd, 1991), brook trout (Salvelinus fontinalis) (Nuhfer and Alexander, 1992) and sand flathead (Platycephalus bassensis) (Lyle et al, 2007). In those studies, smaller fish were believed less likely to deeply engulf a hook because of their smaller mouth size.…”
Section: Discussionsupporting
confidence: 74%
“…Shallow-(lip, mouth) and foul-(outside of mouth) hooking locations are usually associated with much higher PRS rates than deephooking locations (throat, gills, esophagus, gut) (Muoneke and Childress, 1994). In turn, hooking location has been linked to fish length (Lyle et al, 2007;Grixti et al, 2007), hook size (Jordan and Woodward, 1992;Cooke et al, 2005;Grixti et al, 2007), hook type (Skomal et al, 2002;Cooke et al, 2003Cooke et al, , 2005Lyle et al, 2007), angling techniques (active or passive fishing) (Grixti et al, 2007) angler experience and bait type (Erzini et al, 1998;Huse and Soldal, 2000;Broadhurst and Hazin, 2001). Post-release survival for deep-hooked fish in the days and/or weeks of monitoring after capture is typically reported as higher when hooks are left in fish compared to when hooks are removed (Bartholomew and Bohnsack, 2005;Arlinghaus et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The mortality rates (3.6 and 8.9%) of Platycephalus fuscus observed in this study were similar to those recorded for this species in Queensland (6.9%, Brown et al 2006) and P. bassensis in Tasmania (7.6%, Lyle et al 2007), but the underlying causes were apparently different. Similar to numerous other local (Diggles & Ernst 1997, Broadhurst et al 2005 and overseas (Warner 1976, Schill 1996, Aalbers et al 2004) species, both of the previous studies demonstrated a positive correlation between deep hooking and the number of deaths.…”
Section: Discussionsupporting
confidence: 63%
“…Recognition of the need to validate the inherent assumption that the majority of these individuals sustain few subsequent negative impacts has resulted in 2 preliminary studies to estimate mortality and the key contributing factors (Brown et al 2006, Lyle et al 2007). Both studies examined the fate of fish released immediately after conventional angling.…”
Section: Introductionmentioning
confidence: 99%
“…Survival of foul-hooked spotted seatrout (Cynoscion nebulosus) was 92%, which was similar to the survival rate of spotted seatrout hooked in the mouth (90%) and greater than survival rates of spotted seatrout hooked in the gills (25%) and esophagus (5%, James et al 2007). Survival of foul-hooked sand flathead (Platycephalus bassensis) was loo%, which was similar to survival rate of sand flathead hooked in the mouth (99.6%) and greater than the survival rate of sand flathead hooked in the esophagus and stomach (64%, Lyle et al 2007). We found that survival of foul-hooked largemouth bass was 100% (this study), which was similar to the survival rate of largemouth bass hooked in the mouth (98.3%, Wilde and Pope 2008; loo%, this study) and greater than the survival rate of esophagus-hooked largemouth bass (55%, Wilde and Pope 2008).…”
Section: Resultsmentioning
confidence: 68%